2017
DOI: 10.1007/s11101-017-9506-4
|View full text |Cite
|
Sign up to set email alerts
|

High-carotenoid maize: development of plant biotechnology prototypes for human and animal health and nutrition

Abstract: Carolight® is a transgenic maize variety that accumulates extraordinary levels of carotenoids, including those with vitamin A activity. The development of Carolight® maize involved the technical implementation of a novel combinatorial transformation method, followed by rigorous testing for transgene expression and the accumulation of different carotenoid molecules. Carolight® was envisaged as a way to improve the nutritional health of human populations that cannot access a diverse diet, but this ultimate human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Biofortified crops have been also shown to an efficient source of carotenoids for animals. For example, feeding poultry with carotenoid biofortified maize enhanced the accumulation of carotenoids in muscles, skin and egg yolk, and increased liver vitamin A content under lab and farm conditions [262]. In addition, carotenoids from biofortified maize has been shown to protect broilers against coccidiosis without the need for artificial carotenoid additives [263].…”
Section: Are Carotenoids From Biofortified Crops Useful?mentioning
confidence: 99%
See 1 more Smart Citation
“…Biofortified crops have been also shown to an efficient source of carotenoids for animals. For example, feeding poultry with carotenoid biofortified maize enhanced the accumulation of carotenoids in muscles, skin and egg yolk, and increased liver vitamin A content under lab and farm conditions [262]. In addition, carotenoids from biofortified maize has been shown to protect broilers against coccidiosis without the need for artificial carotenoid additives [263].…”
Section: Are Carotenoids From Biofortified Crops Useful?mentioning
confidence: 99%
“…Astaxanthin is the most expensive fish food ingredient added to obtain a desirable pink flesh color of salmon and trout. Biological sources of this ketocarotenoid are not sufficient to meet the global astaxanthin demand [262]. Recently, astaxanthin-biofortified transgenic maize and tomato fruit have been shown to be more efficient in conferring the desired color to egg yolk and salmon flesh, respectively, compared to synthetic astaxanthin additives [41,263]…”
Section: Are Carotenoids From Biofortified Crops Useful?mentioning
confidence: 99%
“…Therefore, a different approach was followed in later experiments, by combining expression of different genes belonging to the carotenoid pathway, which led to substantial β-carotene increases in rice (Ye et al, 2000; Paine et al, 2005; Tian et al, 2019) and potato (Diretto et al, 2007a; Diretto et al, 2007b). A variation of the method was proven in maize; by selecting those favorable alleles that had been verified to alter the metabolic pathway toward β-carotene gave as an end result orange maize seeds with extended β-carotene content (Harjes et al, 2008; Yan et al, 2010; Zhu et al, 2018). However, in some cases, the increased flux into carotenoid biosynthesis can alter or reduce flux to other important pathways, leading to undesired changes (Cazzonelli and Pogson, 2010).…”
Section: Manipulating Orange Gene Toward Carotenoid Accumulationmentioning
confidence: 99%
“…Studies have demonstrated that in humans (Seddon et al, 1994; Snodderly, 1995; Fiedor and Burda, 2014) carotenoids have an important antioxidant and anticancer activity, as well as protector agents against macular degeneration of elderly people (Beatty et al, 2000). Because of their multiple functions, efforts have been made to elucidate carotenoids synthesis and storage in different plant species, and work has been made to fortify staple crops for carotenoid consumption (Zhu et al, 2018; Tian et al, 2019). Carotenoid accumulation in chromoplasts is the result of three independent processes, carotenoid biosynthesis, degradation, and stable storage, which occur at different developmental plant stages (Li and Yuan, 2013; Nisar et al, 2015).…”
mentioning
confidence: 99%
“…Several studies have suggested that carotenoid pigments reduce the oxidative stress in pre‐hatched and post‐hatched birds through different mechanisms, including quench free radicals, activating antioxidant enzymes and inhibiting the signalling pathways (Arain et al., 2018; Changxing et al., 2018; Langi et al., 2018). Birds consumed carotenoid supplemented diet as a part of nutrient improves performance and product quality (Langi et al., 2018; Zhu et al., 2018). Dietary addition of pigments to poultry diet improves the colour of skin, flesh and egg yolk (De Carvalho, Cipolli, Ormenese, Carvalho, & da Silva, 2009; Hamelin, Martinez‐Aleson, & Martínez, 2013).…”
Section: Introductionmentioning
confidence: 99%